A SOCIALIZATION OF HOUSEHOLD ELECTRICAL INSTALLATIONS ACCORDING TO SNI STANDARDS (INDONESIAN NATIONAL STANDARD) TO PREVENT FIRE - Ahmad Faisal; Mhd Erpandi Dalimunthe; Trinidad Daniel Silalahi (Sean Institute, 2023)
The more sophisticated and prosperous human civilization along with the development of technology. The rapid development of technology has resulted in the need for electrical energy sources also increasing. The source of electrical energy is one of the supporting factors for human survival, especially for household or residential electricity needs. One of the functions of electricity in the house is as lighting, apart from that electricity functions as a support for other technologies such as turning on TVs, computers, blenders, cellphone chargers and other electronic equipment. However, the use of electricity often results in accidents such as fires, explosions and damage to electronic equipment caused by several factors such as electrical installation errors in residential homes and improper or non-standard use. This socialization aims to provide understanding to the public to understand the importance of household electrical installation standards in accordance with the Indonesian National Standard (SNI) or General Electrical Installation Requirements (PUIL) to prevent fires and other hazards.